GIS in Mostecká uhelná a.s. - Aleš Fau; Petra Blínová; Tereza Koudelková; Jan Blín; Vladimíra Nechvátalová (Acta Montanistica Slovaca, 2007)
Geographical Information Systems (GIS) were put into full operation by Mostecká uhelná a.s. (Most Mining company) at the beginning of 2006 after two years testing. The implementation of GIS was started in March 2003.The main objective was to make all graphical data as well as their relevant attributes and documents accessible to a wide range of users. The purpose of the implementation of GIS by Mostecká uhelná company is to link different kinds of data and to get a complex view of the area of operation as well as the property of the company.A special emphasis was put on the graphical representation of data during the implementation of GIS. The common tools of GIS do not enable to achieve required correspondence between the mapping documentation and the graphical representation of data. For that reason, special tools were designed and implemented into the standard system of GeoMedia with the aim to meet these requirements of data representation.